Comparison of Characterization in the Novel Sunset & Rosil by Tere Liye and the Novel Sirkus Pohon by Andrea Hirata - Pohan, Jusrin Efendi (Asosiasi Ide Bahasa Kepri, 2025)
One of the most important aspects in a novel is characterization. The author's creativity determines the role of the characters in the story until its climax. Therefore, it is necessary to conduct a kind of characterization analysis in the novel Sunset & Rosil by Tere Liye and the novel Sirkus Pohon by Andrea Hirata. This study was conducted to describe the characterization of the two novels Sunset & Rosil by Tere Liye and the novel Sirkus Pohon by Andrea Hirata. The analysis was carried out by analyzing the content of the novel Sunset & Rosil by Tere Liye and the novel Sirkus Pohon by Andrea Hirata. Data collection was carried out using the technique of noting sentences and paragraphs related to the characterization of the two novels. The data is analyzed and interpreted for each sentence/paragraph to obtain the meaning contained therein. To test the data, data reduction is used by rearranging the data obtained by sorting data that is relevant to the characterization. After the data is interpreted, the data is then analyzed by collecting data, selecting data, and compiling reports. The results of this study show that the characterizations in the novel Sunset & Rosil by Tere Liye and the novel Sirkus Pohon by Andrea Hirata are described as sincere, honest, fair, patient, and forgiving of others. The novel Sirkus Pohon by Andrea Hirata tells about the daily life of the people in one of the villages in Tanjong Lantai, Belitung.